Reducing gun violence in America : informing policy with evidence and analysis (Baltimore, MD : Johns Hopkins University Press, 2013)
"The staggering toll of gun violence-which claims 31,000 U.S. lives each year-is an urgent public health issue that demands an effective evidence-based policy response. The Johns Hopkins University convened more than 20 of the world's leading experts on gun violence and policy to summarize relevant research and recommend policies that are both constitutional and have broad public support. Collected for the first time in one volume, this reliable, empirical research and legal analysis will help lawmakers, opinion leaders, and concerned citizens identify policy changes to address mass shootings, along with the less-publicized gun violence that takes an average of 80 lives every day. Selected recommendations include: Background checks: Establish a universal background check system for all persons purchasing a firearm from any seller. ; High-risk individuals: Expand the set of conditions that disqualify an individual from legally purchasing a firearm. ; Mental health: Focus federal restrictions on gun purchases by persons with serious mental illness on the dangerousness of the individual. ; Trafficking and dealer licensing: Appoint a permanent director to ATF and provide the agency with the authority to develop a range of sanctions for gun dealers who violate gun sales or other laws. ; Personalized guns: Provide financial incentives to states to mandate childproof or personalized guns. ; Assault weapons and high-capacity magazines: Ban the future sale of assault weapons and the future sale and possession of large-capacity ammunition magazines. ; Research funds: Provide adequate federal funds to the Centers for Disease Control and Prevention, National Institutes of Health, and National Institute of Justice for research into the causes and solutions of gun violence. The book includes an analysis of the constitutionality of many recommended policies and data from a national public opinion poll that reflects support among the majority of Americans-including gun owners-for stronger gun policies."--Publisher's website.
Consensus recommendations for reforms to Federal gun policies.
Includes bibliographical references and index.
Keywords: Gun control -- United States; Firearms and crime -- United States; Violent crimes -- United States -- Prevention; Firearms -- legislation & jurisprudence -- United States; Social Control, Formal -- United States; Violence -- legislation & jurisprudence -- United States; Violence -- prevention & control -- United States